A Study of Glucosylceramide Synthase and Glycolytic Pathway Enzymes in Patients with Hypereosinophilia - Lisa Redmond; Paul Kennedy; Colm Buckley; Philip T Murphy (International Journal of Immunotherapy and Cancer Research - Peertechz Publications, 2017)
Glucosylceramide synthase is the rate limiting enzyme in ceramide glycosylation and shifts the balance between ceramide and glycosphingolipids towards proliferation and survival of cancer cells. Increased glucose availability and glycolytic metabolism is preferentially used by cancer cells and has been linked to glycosphingolipid formation. We measured gene expression levels of glucosylceramide synthase and of glycolytic pathway enzymes, glucose transporter 1 and hexokinase II, as well as protein expression of glucosylceramide synthase, on trephine biopsy samples from 13 patients with hypereosinophilia, We found no signifi cant differences in expression levels of any of the enzymes in patients with secondary causes of hypereosinophilia compared to those with either suspected or proven clonal hypereosinophilia.